Evaluating Village Fund Allocation using Effectiveness, Efficiency, and Growth Ratios - Alfian, Ryan Allif; Syafina, Laylan; Nurwani (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to evaluate the performance of Village Fund Allocation (ADD) management in Gampong Lampulo during the 2021–2023 period using three financial ratio approaches: effectiveness ratio, efficiency ratio, and growth ratio. The research addresses a gap in the literature by comprehensively combining these three ratios into a single analytical framework. A quantitative descriptive method with documentation techniques was employed. Data were obtained from the Village Revenue and Expenditure Budget (APBDes) Realization Reports for 2021–2023. The results show that ADD management in Gampong Lampulo was generally effective and efficient, although some fluctuations occurred. The effectiveness ratio ranged from 85.80% to 100%, and the efficiency ratio from 82.64% to 90.78%, falling into the